Computational intelligence based technique for load shedding scheme / Lukman Hakim Hamron - Hamron, Lukman Hakim (2013)
Losses in generation and overloading effect are two phenomena that may occur due to progressing demand at the load side. This may lead to system instability in the forms of voltage and frequency. In order to avoid this problem, the under voltage load shedding scheme can be performed to shed some amount of load in order to avoid blackout. This paper presents computational intelligence technique for load shedding. The study involves the development of fuzzy rules in order to make decision on load shedding. It will determine the amount of load that needs to be shed depending on the measured minimum voltage of the system. The result of this study will show the performance of under voltage load shedding scheme in determining power system stability by shedding some amount of the load demand. The technique has been validated on the IEEE 30-bus system.